Practical guide to using 6Mo austenitic stainless steel - Davison, Ralph M.; Redmond, James D. (Technical series (Nickel Development Institute (Canada)) ;, 1988)
This booklet gives information on the metallurgy, crevice corrosion, and chloride stress corrosion cracking resistance, design, and fabrication as well as specifications and commercial product of alloys 254 SMO,™ AL-6X,™ AL-6XN,™ 1925 hMO (26-6MO) and 20 MO-6.™